PENINGKATAN KINERJA MELALUI PENGEMBANGAN SUMBER DAYA MANUSIA - Yulita; Sri Yanthy Yosepha (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to examine the rational link between improving the performance of employees or members of a particular company or organization. In addition, a review was also carried out in order to find general forms of human resource development within the framework of performance improvement. The method used in this research is descriptive qualitative withliterature study. Theresults of this study are as follows. First, human resources within the scopeof a particular company or organization are human resources in the micro sense. Thereforeefforts to develop it are carried out entirely by the company or organization. Unlike the case with human resources in a macro sense where the state is responsible for human resource development programs through the implementation of the national education system. Second,human resource development is accelerated within this framework in a formal manner. Thismeans that the involvement of employees or members in the human resource developmentprocess is carried out through learningassignments and training programs, both organized by companies and external educational or training institutions. Thus, improving the performance of employees or members can be done through formal resource development through learning assignment programs and training that isrelevant to the needs.